Trypanocidal activity of human plasma on Trypanosoma evansi in mice - Da Silva,Aleksandro Schafer (2012)
This study aimed to test an alternative protocol with human plasma to control Trypanosoma evansi infection in mice. Plasma from an apparently 27-year-old healthy male, blood type A+, was used in the study. A concentration of 100 mg.dL-1 apolipoprotein L1 (APOL1) was detected in the plasma. Forty mice were divided into four groups with 10 animals each. Group A comprised uninfected animals. Mice from groups B, C and D were inoculated with a T. evansi isolate. Group B was used as a positive control. At three days post-infection (DPI), the mice were administered intraperitoneally with human plasma. A single dose of 0.2 mL plasma was given to those in group C. The mice from group D were administered five doses of 0.2 mL plasma with a 24 hours interval between the doses. Group B showed high increasing parasitemia that led to their death within 5 DPI. Both treatments eliminated parasites from the blood and increased the longevity of animals. An efficacy of 50 (group C) and 80% (group D) of human plasma trypanocidal activity was found using PCR. This therapeutic success was likely achieved in the group D due to their higher levels of APOL1 compared with group C.